Adaptation of cultural norms after merger and acquisition based on the heterogeneous agent-based relative-agreement model. (December 2013) - Zhu, Hou; Hu, Bin; Wu, Jiang; Hu, Xiaolin
The subject of norm formation and diffusion has gained lots of attention in social science and organizational science in the last decade. This paper explores how public dissenters in acquired firms can affect success or failure of merger and acquisition (M&A). In the classical relative-agreement model, all individuals observe their neighbors' behavior and update their own opinion and behavior following the same rule. This paper proposes a new heterogeneous relative-agreement model where individuals update their behavior following different rules after M&A. Simulation experiments show that the time shortly after acquisition is a key period to guide the acculturation in a way consistent with the intent of the acquiring firm, and that the risk of cultural norm reversing after acquisition is influenced by several important factors. Some suggestions for guiding the acculturation process after M&A are also provided.